Faktor-Faktor yang Berhubungan dengan Gejala Kelelahan Mata Pada Pengrajin Sarung Tenun Kota Samarinda - Anggriani, Yeni; Ramdan, Iwan M; Lusiana, Dina (Husada Mahakam, 2019)
Eyestrain is affected by several factors as follows the factor from the artisan itself, work factor and working environment factor. This research aims to know correlated factors with eyestrain symptom on woven sarong artisan of Samarinda City. Quantitative research with cross-sectional approach is done on September – October 2018 with total samples of 50 artisans (total sampling). Measuring instruments which are used are questionnaire and lux meter type DX-100. Data analysis uses Phi correlation test with a = 0.05. Research result shows woven sarong artisan who experiences eyestrain symptom as many as (64%), and  woven sarong artisan who does not experience eyestrain symptom (36%). There are correlation between age (p = 0.000) and work time (p = 0.003). There are no correlation between daily working time (p = 0.090) and lighting intensity (p= 0.486). It is suggested to artisans to use toolkit such as magnifiying glass, to manage working time, and break time to minimize eyestrain occurrence. For artisan who uses lamp as main lighting source to pay attention lighting level which is used, in this case is lux lighting.